Abdominal Ectopic Pregnancy and Impaired Postnatal Mammary Gland Development, Consistent With Physiologic Agalactia, in a Wild European Rabbit, Oryctolagus cuniculus - Hughes, Katherine (Frontiers in Veterinary Science, 2019)
A wild European rabbit, Oryctolagus cuniculus, was diagnosed with an abdominal pregnancy due to the presence of a single abdominal lithopedion attached by a thin fibrovascular stalk to the left uterine horn, which was distorted by the tension of the adhesion. Evidence of mineralized remnants, chronic inflammation, and fibrosis in the left uterine endometrium and myometrium suggested that the lithopedion had arisen as a secondary abdominal pregnancy. The right uterine horn contained two macroscopically normal fetuses. The mammary gland exhibited notably retarded development in relation to the size of the fetuses. Histologically, mammary alveoli lacked evidence of intraluminal secretory product, and ducts lacked prominence and contained clusters of small numbers of macrophages. The doe also exhibited mild granulomatous and heterophilic pneumonia with rare intralesional adiaspores, suggesting infection with Emmonsia spp. as an incidental finding. This case documents secondary abdominal pregnancy in a wild lagomorph not subjected to artificial insemination procedures suggested to increase the occurrence of this condition in farmed rabbits. An abdominal pregnancy is one of a number of factors that should be considered as a potential factor in the etiology of impaired postnatal mammary development or reduced milk yield in a breeding doe, although no causative association is demonstrated in this case. Abdominal ectopic pregnancy is one possible differential diagnosis in the investigation of the presence of a palpable abdominal mass or masses in Oryctolagus cuniculus.